The emperor in the Byzantine world
1 online resource (1 volume)
Keywords: The subject of the emperor in the Byzantine world may seem likely to be a well-studied topic but there is no book devoted to the emperor in general covering the span of the Byzantine empire. Of course there are studies on individual emperors, dynasties and aspects of the imperial office/role, but there remains no equivalent to Fergus Millar's The Emperor in the Roman World (from which the proposed volume takes inspiration for its title and scope). The oddity of a lack of a general study of the Byzantine emperor is compounded by the fact that a series of books devoted to Byzantine empresses was published in the late twentieth and early twenty-first centuries. Thus it is appropriate to turn the spotlight on the emperor. Themes covered by the contributions include: questions of dynasty and imperial families; the imperial court and the emperor's men; imperial duties and the emperor as ruler; imperial literature (the emperor as subject and author); and the material emperor, including imperial images and spaces. The volume fills a need in the field and the market, and also brings new and cutting-edge approaches to the study of the Byzantine emperor. Although the volume cannot hope to be a comprehensive treatment of the emperor in the Byzantine world it aims to cover a broad chronological and thematic span and to play a vital part in setting the agenda for future work. The subject of the Byzantine emperor has also an obvious relevance for historians working on rulership in other cultures and periods.